PENINGKATAN APRESIASI SASTRA BERNUASA ISLAMI DENGAN PENDEKATAN RESEPSI SASTRA DI MAN YOGYAKARTA II - Anita Isdarmini (Universitas PGRI Semarang, 2014)
This study aims to: (1) Develop students' attitudes MAN Yogyakarta II more posiitf towards learning literature, and (2) Increase apreisasi nuances of Islamic literature approach literary reception in Yogyakarta MAN II. This research is a class act. Teachers act as a researcher who worked with two collaborators. The action taken is to apply the approach to reception in the learning literature, especially short story Islamic bernusansa. Raised in the learning process as much as possible the characteristics of the approach reception. The learning method used is the approach reception. The learning method used is a combination of various methods: individual assignment and, group discussions, question and answer, presentation, and performance. Implementation of the measures is divided into two cycles. The first cycle includes three action compose contains three learning skills, including: (1) read short stories, (2) listening to stories, and (3) discuss short stories. Cycle II also includes three measures of improvement denagn I. cycle monitoring techniques are applied is participatory observation, interviews, data collection and analysis documents covering the syllabus and assessment system, the student's work, the value of the results of the evaluation, the results of the questionnaire, and photo documentation. The data analysis was done by using descriptive qualitative and quantitative descriptive simple way, namely by comparing the mean value. Improving the quality of the learning process include: (1) student involvement in learning more, (2) The cooperation of students in groups of tasks increases, and (3) the independence of students in individual tasks also increased. As for improving the quality of learning outcomes include: (1) a sense of satisfaction on students increases, (2) the quality of the type and hasi eveluasil increased student learning.Keywords: Increased Appreciation Nuance Islamic literature, Literary Reception